A longitudinal study on sleep quality of patients with stage 4 chronic kidney disease,subject to hemodialysis and peritoneal dialysis - LUO Min-hong; YUAN Li-ping; CHEN Qiu-lian; ZHU Lang-jing; ZENG Hai-ou; CHEN Zhen-wei; WU Qiang; YANG Tie-cheng (Linchuang shenzangbing zazhi)
Objective A longitudinal research was conducted in our center to observe the dynamic change of sleep quality of patients with stage 4 chronic kidney disease(CKD),subject to hemodialysis and continuous ambulatory peritoneal dialysis(CAPD) and to investigate the associated factors.Methods Patients with CKD stage 4(n = 43),hemodialysis(n = 41) and CAPD(n = 44) were included and followed up for 1 year.Pittsburgh Sleep Quality Index(PSQI) and laboratory parameters were evaluated every 6 months.The univariate and multivariate Logistic regression analysis was used to analyze the associated factors.Results There was no significant difference in age,sex,socio-economic factors,smoking,BMI,Charlson comorbidity index and primary renal disease among the three groups(P>0.05).At the baseline and sixth month,the PSQI scores in hemodialysis and CAPD groups were significantly higher than those in CKD stage 4 group(P<0.05).At the twelfth month,there was no significant difference in PSQI scores among the three groups(P<0.05).As compared with the baseline values,the PSQI scores among the three groups at the sixth month were all significantly increased(P<0.05).As compared with the values at sixth month,the PSQI scores in CKD stage 4 group at the twelfth month were significantly increased(P<0.05),and those in hemodialysis and CAPD groups had no significant change.With the dynamic changes of the total PSQI score,hemoglobin,calcium and phosphorus product,intact parathyroid hormone and high-sensitivity C-reactive protein also changed in the three groups.Age(OR=1.83,P=0.01),hemoglobin(OR=1.46,P=0.01),calcium and phosphorus product(OR=1.25,P=0.02),intact parathyroid hormone(OR=1.17,P=0.03),and high sensitivity C-reactive protein(OR=1.32,P=0.04)were significantly related to poor sleep.Conclusions The sleep quality of patients with CKD stage 4,subject to hemodialysis and CAPD progressively deteriorated.Older age,anemia,the disorders of calcium phosphate metabolism and the microinflammatory status are the independent risk factors of poor sleep quality.